Konstruksi Makna Kualitas Hidup Sehat (Studi Fenomenologi pada Anggota Komunitas Herbalife Klub Sehat Ersand di Jakarta) - Endang Susanti; Nur Kholisoh (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This study was intended to get a comprehensive picture of meaning construction in building the quality of healthy life. This research used symbolic interaction theory of George Herbert Mead. The study relied on phenomenological approach under a paradigm of constructivism using interpretative analysis. In-depth interview, observation, and documentation study were conducted to collect data. This study found that the motives of Herbalife community health club Ersanddi members to participate in a healthy life program because they wanted to lose weight and to be physically fit. The meaning of healthy lifestyle for them is to be able to enjoy their life and worship to the Creator without any obstacles. The meaning of healthy life to the members of Herbalife community health club of Ersanddi was influenced by their environment namely significant others and reference groups.